PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA PADA KANTOR PDAM TIRTA BALURAN DI KABUPATEN SITUBONDO - Maulida K, Faradina Pindi; Sari, Lita Permata; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
One of the important factors in the field of human resources is providing compensation and motivation, which are the rights of employees and the company's obligation to support the contributions of workers in order to achieve the goals that have been determined. The purpose of this study was to analyze and examine the effect of compensation on employee performance through work motivation at the PDAM Tirta Baluran office in Situbondo Regency. The population in this study were permanent employees of the PDAM Tirta Baluran office in Situbondo Regency. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that compensation has a significant positive effect on work motivation, compensation has a positive but not significant effect on employee performance, work motivation has a positive significant effect on employee performance, compensation has a significant positive effect on employee performance through work motivation .